Efek Penggunaan Suplemen Ekstrak Daun Jambu Biji (Psidium guajava Linn.) dan Angkak (Monascus purpureus) dalam Meningkatkan Trombosit pada Demam Berdarah Dengue (DBD) di Instalasi Rawat Inap Ilmu Penyakit Dalam RSUP. DR. M. Djamil Padang - Muharni, Septi; Martini, Rose Dinda (Jurnal Penelitian Farmasi Indonesia, 2013)
The clinical study on effect of supplement psidii folium and red fermented rice extract in management for increasing thrombocytes in patientsufferings Dengue Hemorrhagic Fever (DHF) at RSUP. DR. M. Djamil Padang has been done. The research was conducted using quasiexperimental method with pre and post test design. The subjects were 20 patients and willing to give informed consent was included. Patientswith hematology abnormality, heart and lung disease, salicylic acid treatment, severe hemorrhagic condition, and descent consciousness wereexcluded. An amount of thrombocytes were measured every 12 hours in a day. Furthermore, the changes of thrombocytes count from startto end were analyzed using t-independent-test (to analyze the difference of changes between groups) and chi-square (to analyze the responserate between groups). In this trial of 20 subjects, the thrombocytes count of the test group was significantly increased compared with thecontrol group p<0.05 (p=0,0120) and the increasing of thrombocytes response rate in the test group was significantly different from thatin the control group p<0.01 (p=0,0034). As conclusion, the results of this trial have proven that psidii folium and red fermented rice extractcould treat thrombocytopenia.